Legal Analysis of Limited Company Which Was Submitted to Bankruptcy - Suryati, Suryati; Sardana, Layang; Disurya, Ramanata (Nurani, 2022)
The purpose of this study is to analyze the legal consequences caused by a limited liability company being sentenced to bankruptcy. The research method used in this study is the normative legal method. The result of this study is that the result obtained from this study is that the Board of Directors can be held liable both civilly and criminally for the insolvency of a limited liability company. Civil liability may be liability for a lease for losses suffered by a limited liability company in the event of insolvency due to the fault and negligence of the Board of Directors and the company's assets are not sufficient to cover losses due to bankruptcy. Criminal liability in the form of imprisonment in addition to other responsibilities in the form of a forced entity as stipulated in the Insolvency Law, while the legal consequences of insolvency for a limited liability company can be in the form of termination of business relations from the company by creditors and curators, or even dissolved by the District Court on the grounds of creditors on the basis of the company being unable to pay debts after being declared bankrupt.